Assessing complex evolving cyber-physical systems (case study: smart medical devices). (2019) - Sliwa, Jan
Our environment becomes permeated by intelligent devices and systems that directly interact with physical objects, including our bodies. Such cyber-physical systems produce immense amount of data that can be stored and analysed. Those data are of value as 'actionable knowledge' only if the process of collection, cleaning, and analysis is well managed and unbiased. The system has to be well understood and the statistical questions properly formulated, otherwise spurious correlations can be misinterpreted as causation. A major challenge is the changing nature of the technical systems, of the environment in which they operate and of the humans who use them. Those interacting subsystems manifest novel dynamic behaviour, different from purely digital systems. We will discuss the general problems of assessing the quality of cyber-physical systems and use smart medical devices as a case study.